2009
DOI: 10.1080/01431160802509009
|View full text |Cite
|
Sign up to set email alerts
|

Can Landsat imagery detect tree line dynamics?

Abstract: Prior research on tree line dynamics has primarily been based on field inventory data, and little is known about the potential for using remotely sensed imagery to detect change. The present study developed a new methodology by combining remote sensing and field survey data to examine dynamics of the pristine forest in the tree line area on Changbai Mountain in Northeast China over the past two decades. The new method normalized remote sensing data by using the adjacent old-growth coniferous forest (close to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 40 publications
(35 reference statements)
1
21
0
1
Order By: Relevance
“…Ecotone edges were identified by various hierarchical methods based on wavelet analysis and by bivariate techniques of edge detection, using filters and kernels [28,29]. Both field measurements and remote sensing data are used to detect and describe ecotone properties and analyze changes of their boundaries [30][31][32][33][34][35].…”
Section: Methodsmentioning
confidence: 99%
“…Ecotone edges were identified by various hierarchical methods based on wavelet analysis and by bivariate techniques of edge detection, using filters and kernels [28,29]. Both field measurements and remote sensing data are used to detect and describe ecotone properties and analyze changes of their boundaries [30][31][32][33][34][35].…”
Section: Methodsmentioning
confidence: 99%
“…Pixel-based [Tattoni et al, 2010] and object-oriented [Sitko et al, 2008] classification approaches, both supervised [Bader et al, 2008;Kral, 2009] and unsupervised [Klasner et al, 2002;, of multispectral aerial and satellite imagery, are also used. Some studies base mapping on screen image-interpretation [Zhang et al, 2009]. Ground surveys, mainly performed by GNSS (Global Navigation Satellite Systems) [Groen et al, 2012;Ropars et al, 2012] are widely used to collect ground truth samples that are in turn used to train classifiers and validate classification results.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, optical remote sensing techniques, in particular, are recognized as an essential tool for treeline ecotone observation, with specific focus on its position and dynamics. This is generally achieved by using bi-dimensional primary datasets such as satellite data [Driese, 1997;Milah et al, 2007;Bader, 2008;Zhang et al, 2009;Panigraphy et al, 2010], digital aerial orthoimages [Stueve et al, 2009;Ropas et al, 2012], and current and historical maps [Mast et al, 1997;Bryn, 2008], all managed by GIS (Geographic Information Systems) [Paulsen and Korner, 2001;Stueve et al, 2009]. Additionally, some basic terrain features (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies also showed that tree density and biomass production increased at timberlines from the past to the present, although the altitudinal location of timberlines and treelines did not change (Camarero and Gutierrez 2004;Zhang et al 2009;Liang et al 2011). For example, increase in biomass production was recognized for 26.7 % of tree species examined by using meta-analysis (Lin et al 2010).…”
Section: Discussionmentioning
confidence: 99%